India, Brazil, and public health: Rule-making through south–south diffusion in the intellectual property rights regime? - Omar Ramon Serrano Oswald; Mira Burri (Regulation & Governance, 2020)
This article analyzes the domestic drivers of regulatory state formation in India and Brazil and its consequences for the global rules governing pharmaceutical patents. We first analyze Indian and Brazilian politics of regulatory state formation; then, in light of the extent to which the two countries have built regulatory capacity and capability in the field of patent regulation, we explore whether and how they have been able to influence the existing intellectual property regime in health. We look into India's Section 3(d) and Brazil's prior consent requirement. Whereas India's Section 3(d) regulation has gained international regulatory influence by diffusing to other developing countries, the same cannot be said for Brazil's prior consent regulation, which has been caught by policy-reversals. The transition toward regulatory states in emerging countries is a bulky road and does not progress in linear ways. However, once regulatory capacity and capability have been solidified, domestic policy innovations can become internationally influential.
Keywords: 330; Brazil; India; intellectual property; public health; rule-making; south–south diffusion